Pembuatan Video Edukatif Mengenai Sistem Kerja Listrik Tenaga Bayu - Talitha Naurah Rimanda; Ririn Agustin; Mochamad Zacky Ilham Halim; Naufal Abrar Wijaya; Muhammad Daffa Aldiansyah; Didik Aribowo (Prosiding Seminar Nasional Ilmu Pendidikan, 2026)
Rising electricity demand and the environmental impact of fossil fuels have accelerated the need for renewable energy development, particularly through Wind Power Plants (WPP). However, public understanding of WPP systems remains low due to the lack of interactive learning media. This study developed an educational video combining animation, narration, and illustrations to explain WPP components, the wind-to-electricity conversion process, and its benefits. Results show the video effectively improves renewable energy comprehension and holds strong potential as a self-directed learning medium to support energy literacy in Indonesia